Uso de antibióticos en pacientes neutropénico febriles post quimioterapia del servicio de hematología del hospital nacional edgardo rebagliati martins.” - Castañeda Cachay, Julio Eduardo (2008)
Authors: Julio Eduardo Castañeda Cachay and Julio César Vásquez Chacón, thesis: "Use of Antibiotics in Febrile Neutropenic Patients post Chemotherapy of Service of Hematology the National Hospital Edgardo Rebagliati Martins' Advisor: Mg. Roberto Ybañez Julca, 42 pages, 2008, Faculty of Pharmacy and Biochemistry, National University of Trujillo. It made the following problem: ¿what is the use of antibiotics in febrile neutropenic patients post chemotherapy of service of Hematology the National Hospital Edgardo Rebagliati Martins? The material of the study consists of 56 patients with diagnosis of leukemia that received chemotherapy and presented a febrile neutropenia syndrome. Obtaining the sample was carried out with help from the formula of sample size. The sample was classified according to neutropenia high and low risk analyzed the results in these 2 groups. The paper analyzed and evaluated the use of antibiotics and antifungal in febrile neutropenic patients after chemotherapy, the nature of its use, also found the best therapy for the eradication of infection, the so-called cure rate, it according to each type of neutropenia and finally identified the major etiologic agents isolated from these patients